Hypersensitivity reactions to metronidazole - García-Rubio, Isabel; Martínez-Cócera, Consuelo; Santos Magadán, Sara; Rodríguez-Jiménez, Beatriz; Vázquez-Cortés, Sonia (Allergologia et immunopathologia, 2006)
Hypersensitivity reactions to metronidazole are infrequently described. However, we believe that such reactions are increasing due to growing use of the drug for the treatment of amebiasis and anaerobe infections combined with other antibiotics. The present study assesses the need for oral provocation in patients with probable hypersensitivity reactions to metronidazole. We performed cutaneous prick tests with spiramycin and metronidazole as well as epicutaneous tests with metronidazole at different concentrations in four patients with cutaneous reactions to Rhodogil (metronidazole plus spiramicyn). Controlled oral challenges were then carried out with placebo using erythromycin, spiramycin and metronidazole except in the last patient due to a positive prick test. Only one patient showed a positive metronidazole prick test. The epicutaneous tests were negative. All patients tolerated erythromycin and spiramycin up to therapeutic doses. Oral provocation with metronidazole proved positive, the first patient presenting a delayed exanthema and the other two early erythema and itching. We present four cases of cutaneous exanthemas caused by metronidazole (two early and two delayed) and probably mediated by an immune mechanism which we have only been able to demonstrate in one case. Taking into account the low sensitivity of the cutaneous tests (prick tests and epicutaneous tests), oral provocation must be considered the "gold standard" for establishing the diagnosis in many cases of hypersensitivity reactions to metronidazole.